1998
DOI: 10.1073/pnas.95.8.4463
|View full text |Cite
|
Sign up to set email alerts
|

The lethal mutation of the mouse wasted ( wst ) is a deletion that abolishes expression of a tissue-specific isoform of translation elongation factor 1α, encoded by the Eef1a2 gene

Abstract: We have identified the mutation responsible for the autosomal recessive wasted (wst) mutation of the mouse. Wasted mice are characterized by wasting and neurological and immunological abnormalities starting at 21 days after birth; they die by 28 days. A deletion of 15.8 kb in wasted mice abolishes expression of a gene called Eef1a2, encoding a protein that is 92% identical at the amino acid level to the translation elongation factor EF1␣ (locus Eef1a). We have found no evidence for the involvement of another g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 26 publications
8
145
0
Order By: Relevance
“…Thereafter, eEF1A-1/EF-1α is replaced in the brain, heart, and skeletal muscles by its homologue, eEF1A-2/S1; the reason for this transition, as well as the localization of eEF1A-2/ S1 in different cell populations of the central nervous system (CNS), remain to be characterized. Absence of eEF1A-2/S1 caused by partial deletion of the gene, characterized in spontaneous wasted (wst/wst) mutant mice, is lethal in less than 30 days after birth [2], and is postulated to occur as a result of the absence of elongation factor 1A in brain, heart, and skeletal muscle following the developmental switch [7]. Heterozygous mice (+/wst) do not display any phenotype or abrogated longevity and have a normal pattern of protein expression, similar to wild-type (+/+) animals.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, eEF1A-1/EF-1α is replaced in the brain, heart, and skeletal muscles by its homologue, eEF1A-2/S1; the reason for this transition, as well as the localization of eEF1A-2/ S1 in different cell populations of the central nervous system (CNS), remain to be characterized. Absence of eEF1A-2/S1 caused by partial deletion of the gene, characterized in spontaneous wasted (wst/wst) mutant mice, is lethal in less than 30 days after birth [2], and is postulated to occur as a result of the absence of elongation factor 1A in brain, heart, and skeletal muscle following the developmental switch [7]. Heterozygous mice (+/wst) do not display any phenotype or abrogated longevity and have a normal pattern of protein expression, similar to wild-type (+/+) animals.…”
Section: Introductionmentioning
confidence: 99%
“…The encoded proteins are 92% identical and 98% similar. Whereas lack of eEF1A2 gives rise to the wasted mouse phenotype (Chambers et al, 1998), which involves motor neuron degeneration , inappropriate overexpression has now been linked to cancer. Anand et al (2002) showed that eEF1A2, while not normally expressed in ovary, is expressed in 30% of ovarian tumours .…”
mentioning
confidence: 99%
“…The near-ubiquitous form, eEF1A1, is expressed in all tissues throughout development but is absent in adult muscle and heart expressing eEF1A2 instead [58,59]. eEF1A2 is also found in some other cell types including large motor neurons, islet cells in the pancreas and enteroendocrine cells in the gut [60,61]. Despite sharing 92% sequence identity, paralogous human eEF1A1 and eEF1A2 have different functional profiles.…”
Section: Eukaryotic Elongation Factor 1amentioning
confidence: 99%